The Development of a Competency Testing Systems: Adopting TAM to Explore User’s Acceptance - Saputra, Ibrahim Wahyu; Budiyanto, Cucuk Wawan; Hatta, Puspanda (IJIE (Indonesian Journal of Informatics Education), 2017)
The main problems of learning evaluation using paper based-test are inefficient time and cost. Technology can be used as a system to evaluate the learning process. Using technology can save time and cost of implementing learning evaluations. The aims of this study are to create a software product that can be used to evaluate the learning process. This software product is designed to be used by the test organizer or test committee, the teachers and the students (test takers). This software product was developed using Waterfall Model with five stages of development; communication, planning, modeling, construction, and deployment. The testing was conducted by using Blackbox Method and TAM Theory by considering the aspect of usefulness and the aspect ease of use. The analysis was based on the flow of the current test system. The web-based platform enables ease of access for conducting work in various places. According to the result, the Developed Skills Competency Test System is accepted and can be used by the user as an evaluation system.